On taxpayers' reactions to taxation and on tax shift (Ius Novum, 2019)
Numerous governments’ growing interest in extending the tax base can be observed. The article discusses the conditions determining taxpayers’ attitudes and their reactions to taxation and the mechanisms of their most common conduct, i.e. tax shift. It takes into account the Polish scientists’, Adam Krzyżanowski’s and Roman Rybarski’s, output in the area in the twenty-year interwar period, as well as the contemporary experience with some new types of tax, such as bank tax that was imposed on some financial institutions.
Keywords: elasticity of demand; tax limits; indirect tax; direct tax; tax progressiveness; tax shift; taxpayers’ reactions; tax avoidance; tax evasion; tax rates